Clinical and Pathogenetic Assessment of Relationships Between the Dynamics of Body Weight Changes and Atrial Fibrillation in Patients with Primary Obesity - E. A. Praskurnichiy; O. I. Morozova (Архивъ внутренней медицины)
Aims. To evaluate the impact of body weight dynamics on the clinical course of atrial fibrillation in obese patients.Materials and methods. The study included 101 primary obese patients with paroxysmal or persistent atrial fibrillation. Study design: a retrospective, single-center, comparative study. Retrospectively аccording to the he body weight dynamics, patients were divided into 3 groups: those who increased their body weight by >3 % (Group 1, n=40), maintained their initial body weight by ±2.9 % (Group 2, n=29), and reduced their initial body weight by >3 % (Group 3, n=32). Follow-up examinations by a doctor were carried out at least once every 6 months for minimum 36 months. Change in AF type was determined by disease patterns and 7-day Holter monitoring results. The groups were comparable in gender (p=0,9267), age (p=0,3841), height (p=0,8900), and disease form (Paroxysmal atrial fibrillation /Persistent atrial fibrillation) (p=0,8826), the severity of symptoms on the European Heart Rhythm Association score of atrial fibrillations (p=0,8687) and systolic blood pressure at the beginning of the study (p=0,4500).Results. At the final control examination, the body weight of patients in Group 1 increased by an average of 11,4 [9,3; 13,1] kg (р <0,001*), while weight loss in Group 3 averaged -6,2 [-8,4; -5,3] kg (p <0,001*). The decrease in body weight of Group 2 patients was insignificant (p=0,5377) and amounted to -0,1 [-2,0; 1,3] kg. The progression of the disease from paroxysmal to persistent form was observed among 15 (37 %) patients in Group 1, 9 (31 %) patients — in Group 2, 2 (6 %) patients — in Group 3 (p=0,0079*). The regression of arrhythmia from persistent to paroxysmal form was not registered in group 1 (0 %), in group 2, the reverse development of the disease was noted in 1 patient (3 %) and in group 3 — in 6 patients (19 %) (p=0,0053*). There were no free from AF patients in Group 1 at the final follow-up, while 2 (7 %) patients were free from AF in Group 2 and 7 (22 %) — in Group 3 (р=0,0047*). In patients undergoing ablation, procedural success was determined after a 3-month blind period. The need for interventional procedures to restore the sinus rhythm and their multiplicity when comparing the groups did not differ significantly. However, in a pairwise comparison, the difference between groups 1 and 3 of participants was statistically significant (p=0,0079* and p=0,0374*, respectively). Conclusion. This study demonstrates the relationships between the dynamics of body weight and the clinical course of atrial fibrillation. The progression of obesity leads to the progression of the disease. Weight-loss management reverses the type and natural progression of AF, improves the prognosis and the course of disease, regardless of other significant risk factors, increases the anti-arrhythmic therapy effect and the effect of interventional treatment.